2020
DOI: 10.1080/00036846.2020.1827138
|View full text |Cite
|
Sign up to set email alerts
|

Nexus between rural nonfarm income and agricultural production in Bangladesh

Abstract: Evidence from the rural livelihood literature shows that farm households in developing countries engage in nonfarm employment to supplement their household income. This raises the question of whether nonfarm income complements or competes with agricultural production due to a possible shift in farm household labour to nonfarm employment. Using survey data, this study examines the impact of rural nonfarm income on farm households' agricultural production in Bangladesh. Applying the instrumental variable Tobit m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…These results suggest that possible complementary and substitution effects of nonfarm activities may offset each other in the case of Tanzania. As such, our results are consistent with the findings reported by Amare and Shiferaw (2017) in the case of Uganda, but contrary to that of Huang, Wu, and Rozelle (2009) and Mondal et al (2021) in the case of China and Bangladesh, respectively, who conclude that income from nonfarm activities can improve agricultural production by relaxing liquidity constraints.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results suggest that possible complementary and substitution effects of nonfarm activities may offset each other in the case of Tanzania. As such, our results are consistent with the findings reported by Amare and Shiferaw (2017) in the case of Uganda, but contrary to that of Huang, Wu, and Rozelle (2009) and Mondal et al (2021) in the case of China and Bangladesh, respectively, who conclude that income from nonfarm activities can improve agricultural production by relaxing liquidity constraints.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Mondal, Selvanathan, and Selvanathan (2021) using a cross‐sectional survey data from Bangladesh found that nonfarm income has a positive income effect on agriculture, which they explain through a mechanism related to the relaxation of the liquidity constraint enabling farmers to buy more inputs.…”
Section: Theoretical Perspectives and Empirical Reviewsmentioning
confidence: 96%
“…Although labor migration contributes to rural income growth, it also generates a series of issues, such as farm labor shortage and rising farm labor wages, that challenge sustainable agricultural production. As farm machinery can substitute farm labor and potentially save production costs by improving farm production efficiency (Liu et al, 2014;Ma et al, 2021;Mano et al, 2020;Mondal et al, 2021;Olmstead and Rhode, 2014;Wang et al, 2016;Zhou et al, 2018), the development of farm machinery has been growing in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Economic conditions and income strategies reflect differences in farmers' purchasing power for agricultural materials, which directly affect agricultural production decisions [30,31]. Indicators of cash income, household deposits, access to cash credit, and the composition of the family farm's income were considered in this study.…”
Section: Variables Selectionmentioning
confidence: 99%